Importance of subclinical mastitis diagnosis and its economic impacts on dairy properties - literature review - Ramos, Fernando Silva; Fonseca, Lysandra Martineli; Sousa, Joerberson Caixeta de; Almeida, Sabrina Silva; Borges, Leandra Aparecida Leite (Revista Coleta Científica, 2017)
Worldwide, mastitis is the disease that exerts the greatest importance on milk quality, as it causes decreased production, loss of milk quality and glandular parenchyma function. The subclinical form determines the greatest economic losses due to the high prevalence (44.9% to 97%) and reduction of milk production between 25.4 and 43%, being 15 to 40 times more frequent than the clinical form, the majority of the estimates indicates that, on average, an affected quarter results in a 30% reduction in its productivity, and an affected cow loses 15% of its production during lactation. The losses can be expressed by the decrease in production, in the alteration of the components that interfere in the process of manufacture of dairy by-products, animal disposal and replacement rates, and treatments of affected cows. Subclinical mastitis has no visible changes in the mammary gland or milk, but the composition of this product undergoes considerable changes in its elements, such as an increase or decrease in chlorine (Cl), sodium (Na) ions. The main methods of diagnosis of subclinical mastitis are: the California Mastitis Test (CMT) and the Somatic Cell Count (CCS) of the individual mammary quarters, methods that allow the producer to make decisions, such as establishing a milking line or measures prophylactics that prevent the spread by the herd.